Discourse of a Historical Person: The Image of Genghis Khan in Kazakh, Turkish and Kyrgyz Literature - Ashirbekova, A.; Zhumagulov, A.; Zhakulayev, A.; Rustemova, Zh.; Ibraeva, A.; Tleubekova, B.; Zhussupova, A.; Toleubayeva, K. (Forum for Linguistic Studies, 2025)
The purpose of this study is to compare the portrayal of Genghis Khan, a significant world historical figure, in the works of Kazakh, Turkish, and Kyrgyz writers. Specifically, it examines Rakhimzhan Otarbayev’s Tears of Genghis Khan, Abdullah Ziya Kozanoglu’s Red Flag, and Chingiz Aitmatov’s White Cloud of Genghis Khan. This study employs postcolonial theory and the method of interpretation to analyze how each author presents Genghis Khan’s image within their respective cultural and historical contexts. The research highlights the differences in how Genghis Khan’s personality and legacy are depicted across these works. In Tears of Genghis Khan, Kazakh writer Rakhimzhan Otarbayev explores the human aspects of Genghis Khan, portraying not only his fierce and dominant persona but also his internal struggles, emotional suffering, and existential dilemmas. In contrast, Turkish writer Abdullah Ziya Kozanoglu’s Red Flag presents a nationalist image of Genghis Khan, emphasizing his role as a unifying leader of the Turkic world. Meanwhile, in White Cloud of Genghis Khan, Kyrgyz writer Chingiz Aitmatov delves into the psychological dimensions of Genghis Khan, reflecting on his inner conflicts, vision, and moral dilemmas. This comparative study demonstrates how historical narratives are shaped by national perspectives and cultural influences. It also reveals how the legacy of Genghis Khan continues to be a subject of debate and reinterpretation, reflecting broader historical and ideological shifts in Kazakh, Turkish, and Kyrgyz literature.
Keywords: Genghis Khan; Historical Discourse; Postcolonialism; Historical Figure; Interpretation